2002
DOI: 10.1159/000052838
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis in the Very Elderly

Abstract: Background: Whatever may be their clinical presentation, vasculitis syndromes (VS) have a bad prognosis in the very elderly. Objective: The aim of this work was to study VS particularities in very old people. Most published studies on VS in elderly people concern patients older than 60 years; studies concerning very old patients are unusual. Methods: We studied retrospectively subjects older than 75 years with a diagnosis of VS from the Departments of Geriatrics and Internal Medicine at Dijon University Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Older SNV patients are more fragile and their outcomes were reported to be worse than those of younger populations in previous series (2)(3)(4)(5)(6). A recent retrospective study from Spain (Registro Español de Vasculitis Sistémicas [REVAS]) and our own findings showed that SNV in this older population is severe at diagnosis, often with advanced renal involvement, and high treatment-related morbidity and mortality (24).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Older SNV patients are more fragile and their outcomes were reported to be worse than those of younger populations in previous series (2)(3)(4)(5)(6). A recent retrospective study from Spain (Registro Español de Vasculitis Sistémicas [REVAS]) and our own findings showed that SNV in this older population is severe at diagnosis, often with advanced renal involvement, and high treatment-related morbidity and mortality (24).…”
Section: Discussionmentioning
confidence: 61%
“…A previous retrospective study by our group showed that patients aged 65 years or older who were diagnosed as having systemic necrotizing vasculitis (SNV; polyarteritis nodosa [PAN], granulomatosis with polyangiitis [Wegener's] [GPA], microscopic polyangiitis [MPA], or eosinophilic GPA [Churg‐Strauss] [EGPA]) had poorer outcomes than their younger counterparts, mainly because they developed more frequent and/or serious adverse events (SAEs; 68% versus 13%) while receiving conventional therapy . Several other groups have reported similar findings . Therefore, it is a common recommendation or practice to diminish, by up to one‐third, the dose of the most potent induction immunosuppressant, e.g., cyclophosphamide (CYC), for patients aged 65 years or older .…”
mentioning
confidence: 82%
“…Literature on secondary causes, management, and outcome for systemic vasculitis in elderly is scanty with one study reporting only six patients and high mortality. [ 13 ] The various etiological factors are categorized into drugs, infections, connective tissue diseases, malignancies, and paraneoplastic small vessel vasculitis. [ 2 4 13 14 15 16 ] While certain type of vasculitis can have a concurrent association of malignancies, certain malignancies can also present as vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] The various etiological factors are categorized into drugs, infections, connective tissue diseases, malignancies, and paraneoplastic small vessel vasculitis. [ 2 4 13 14 15 16 ] While certain type of vasculitis can have a concurrent association of malignancies, certain malignancies can also present as vasculitis. [ 17 ] In a previous case series of 12 patients who were diagnosed to have vasculitis and cancer within a duration span of 12 months out of 15 million patients presenting to Cleveland Clinic, 6 had solid organ tumors, 4 had lymphoma, and the other 2 had leukemia and multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation